2017
DOI: 10.5200/sm-hs.2017.104
|View full text |Cite
|
Sign up to set email alerts
|

Moterų, Sergančių Krūties Vėžiu, Gyvenimo Kokybė

Abstract: Raktažodžiai: gyvenimo kokybė, krūties vėžys. SantraukaKrūties vėžys jau daugelį metų yra dažniausia moterų onkologinė liga bei opiausia ir aktualiausia jų sveikatos problema. Krūties vėžio, kaip ir kitų onkologinių ligų, klinikinių baigčių rezultatai, tokie kaip išgyvenamumas ir su sveikata susijusi gyvenimo kokybė, yra vieni svarbiausių sveikatos priežiūros efektyvumo ir kokybės kriterijų. Sergančiųjų krūties vėžiu su sveikata susijusios gyvenimo kokybės tyrimai apima fizinę, psichologinę ir socialinę tiriam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Researchers also focus on the assessment of older adults' improved health, in addition to socialisation as a learning impact aspect. Studies on the impact of learning on the older adults` quality of life conducted in 2015 and 2018 (Sučylaitė et al, 2015;Sėlenienė, 2021) have confirmed that older adults see learning as an opportunity to turn run their lives along a better line, to lead a more informed life, and, in this way, learn to manage performance impairments due to emotional limitations. Measuring overall health status of older adults in different cities, researchers found that older people in cities with active Third Age Universities rated their health better.…”
Section: Society Integration Educationmentioning
confidence: 96%
“…Researchers also focus on the assessment of older adults' improved health, in addition to socialisation as a learning impact aspect. Studies on the impact of learning on the older adults` quality of life conducted in 2015 and 2018 (Sučylaitė et al, 2015;Sėlenienė, 2021) have confirmed that older adults see learning as an opportunity to turn run their lives along a better line, to lead a more informed life, and, in this way, learn to manage performance impairments due to emotional limitations. Measuring overall health status of older adults in different cities, researchers found that older people in cities with active Third Age Universities rated their health better.…”
Section: Society Integration Educationmentioning
confidence: 96%